The Effect of Job Satisfaction on Teacher Performance: The Mediating Role of Decision Making - Yuliandra, Yuliandra; Sujadi, Eko; Meditamar, Muhd Odha (UMSU, 2024)
The low performance of teachers is one of the problems in education that can hinder the achievement of educational goals. This study aims to examine the influence of job satisfaction on teacher performance mediated by decision making. A quantitative approach with a survey method was used in this study. The respondents of this study were two hundred and twenty-six elementary school teachers in Sungai Penuh City who were civil servants. They were asked to fill out the Minnesota Satisfaction Questionnaire (MSQ), Decision Making Scale, and Job Performance Scale, which were modified from Employee Performance Assessment. The cause-effect relationships of the variables were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The research findings revealed that job satisfaction and decision making have an influence on teacher performance. Additionally, decision making also plays a significant mediating role in the relationship between job satisfaction and performance. The results of this study have several important implications for improving teacher performance. Efforts to develop good decision-making skills through training and coaching can help enhance teacher performance. School management needs to provide the necessary support and resources for teachers to make effective decisions.